Getting to 100% renewables: operating experiences with very high penetrations of variable energy resources. Issue 19 (17th February 2021) - Lew, Debra; Bartlett, Drake; Groom, Andrew; Jorgensen, Peter; O'Sullivan, Jon; Quint, Ryan; Rew, Bruce; Rockwell, Brad; Sharma, Sandip
Abstract : This study examines experiences of grid operators to successfully integrate very high penetrations of wind and solar photovoltaic (PV) resources. The variability of these resources creates challenges in balancing the system generation and demand, and ensuring resource adequacy and essential reliability services. The inverter‐based nature of wind and solar PV leads to challenges in frequency, transient, and small‐signal stability. In this study, seven system operators demonstrate the ability to manage these challenges in a variety of power systems, from stand‐alone island systems to larger island systems that are interconnected to neighbours, to balancing authorities that are strongly interconnected within very large synchronous systems. They operate within a variety of market constructs, from full regional transmission operators to vertically‐integrated utilities. All are experiencing increases in the penetration of inverter‐based, variable energy resources and finding creative solutions to these challenges.